[PP.26.22] DIASTOLIC NOCTURNAL HYPERTENSION IS ASSOCIATED WITH NON-DIPPING STATUS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2017) - Velmakin, S.; Troitskaya, E.; Villevalde, S.; Kobalava, Z.
Abstract : Objective: Rheumatoid arthritis (RA) is associated with increased cardiovascular risk. Nocturnal hypertension and non-dipping status are important determinants of cardiovascular mortality and morbidity. The aim of the study was to assess the prevalence of nocturnal hypertension and its associations in patients with RA. Design and method: 58 patients with RA (EULAR 2010) without known cardio-vascular disease were examined (76% females, age 55, 9 ± 15, 8 years, 10% smokers, 56% arterial hypertension (AH), 34% dyslipidemia). Median duration of RA was 8, 5 years (IQR 3–16). Seropositive RA was diagnosed in 69%. Median CRP was 5 mg/dl(IQR 1, 6–22 mg/dl), median rheumatoid factor (RF) −46, 5 IU/ml (IQR 14–207 IU/ml). All patients received disease-modifying antirheumatic drugs, 38% - biological treatment. All patients with AH received antihypertensive treatment. 24-h peripheral and central BP monitoring was performed (BPLab Vasotens, «Petr Telegin»). Arterial stiffness was assessed by applanation tonometry (Sphygmocor, AtCor, Australia). P < 0.05 was considered significant. Results: Mean office BP was 126 ± 19/78 ± 11 mmHg. Mean PWV-8, 5 ± 2, 7 m/s. The dipping states were as follows: non-dipping in 60, 3% patients, dipping – in 12, 1%, extreme dipping – in 8, 6% and reverse dipping in 11 (19%). Median of nocturnal fall in systolic BP was 3, 5% (IQR 0–9%). Isolated nocturnal AH was observed in 20, 7% pts. We analysed 2 groups according to nocturnal fall of BP:G1(dipping −>10%) – 72, 4% pts and G2(non-dipping− <10%.) –27, 6% pts. Non-dippers were older (56, 7 ± 16, 2 vs 49 ± 12, 5 years), more often were smokers (20 vs 0%), had higher BMI (25, 4 ± 6, 0 vs 22, 3 ± 5, 1 kg/m 2 ), median duration of AH and RA (1, 5; IQR 0–11 vs 0; min 0, max 1 years and 10; IQR 7–19vs2, 5; IQR 2–6, 5 years, respectively), PWV (8, 6 ± 2, 8 vs 7, 2 ± 2, 1 m/s), nocturnal BP(120 ± 13/70 ± 10 vs 104 ± 9/59 ± 4 mmHg), p < 0, 05 for trend. There were significant correlations between nocturnal fall in SBP and RA duration (r = −0, 3), central BP (r = 0, 2 for SBP and DBP), night SBP and DBP (r = −0, 3 and −0, 5 respectively), p < 0, 05 for trend. Increased central office DBP and night DBP were significant predictors of non-dipping state (beta = −3, 7, p = 0, 008 and −0, 7, p < 0, 0001 respectively). Conclusions: The majority of patients with RA is characterized by non-dipping state. Diastolic nocturnal hypertension is a significant predictor of non-dipping in this patient population.